2018
DOI: 10.5194/acp-18-11779-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modelling studies of HOMs and their contributions to new particle formation and growth: comparison of boreal forest in Finland and a polluted environment in China

Abstract: Abstract. Highly oxygenated multifunctional compounds (HOMs) play a key role in new particle formation (NPF), but their quantitative roles in different environments of the globe have not been well studied yet. Frequent NPF events were observed at two "flagship" stations under different environmental conditions, i.e. a remote boreal forest site (SMEAR II) in Finland and a suburban site (SORPES) in polluted eastern China. The averaged formation rate of 6 nm particles and the growth rate of 6-30 nm particles were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…The OS c observed in Beijing is also higher than that seen in the boreal forest environment of Hyytiälä, despite extremely low NO x concentrations, likely due to low temperature conditions dominating in those conditions (Schobesberger et al, 2013). These degrees of oxidation relatively similar to those seen in other, cleaner environments are likely due to an interplay between the higher temperatures facilitating rapid hydrogen abstractions (Crounse et al, 2013;Quéléver et al, 2019) and the higher concentrations of NO x , HO q 2 , and other RO q 2 molecules terminating the autoxidation sequence more efficiently (Praske et al, 2018;Rissanen, 2018;Garmash et al, 2019).…”
Section: Other Measurementsmentioning
confidence: 53%
See 2 more Smart Citations
“…The OS c observed in Beijing is also higher than that seen in the boreal forest environment of Hyytiälä, despite extremely low NO x concentrations, likely due to low temperature conditions dominating in those conditions (Schobesberger et al, 2013). These degrees of oxidation relatively similar to those seen in other, cleaner environments are likely due to an interplay between the higher temperatures facilitating rapid hydrogen abstractions (Crounse et al, 2013;Quéléver et al, 2019) and the higher concentrations of NO x , HO q 2 , and other RO q 2 molecules terminating the autoxidation sequence more efficiently (Praske et al, 2018;Rissanen, 2018;Garmash et al, 2019).…”
Section: Other Measurementsmentioning
confidence: 53%
“…ation are much lower. HOM formation is largely dependent upon VOC concentration, oxidant concentration (which will be lower if solar radiation is lower, especially in the case of OH q , the main oxidant of aromatic species especially), and temperature (as H shifts are highly temperature-dependent) (Quéléver et al, 2019), as well as losses by RO q 2 termination before a molecule can become HOM and losses to condensational sink. The low HOM concentration is likely due to these lower temperatures and weaker solar radiation not facilitating HOM formation.…”
Section: Diurnal Trends Of Homsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energies vary for autoxidation of different RO 2 from α-pinene ozonolysis between 22 and 29 kcal mol −1 (Rissanen et al, 2015), leading to varying autoxidation rates at different temperatures (Roldin et al, 2019). It should be noted that the temperature dependence in PRAM is the first of its kind but needs further evaluation using recent measurements of HOM formation at different temperatures (e.g., Quéléver et al, 2019).…”
Section: Malte (Model To Predict New Aerosol Formation In Lowermentioning
confidence: 99%
“…These results are in good agreement with observations made by Kristensen et al (2017), who observed an increasing contribution of SVOCs at subzero temperatures of 258.15 K, which decrease the fraction of SOA formed from ELVOCs. Again, it should be noted that the temperature dependence of peroxy radical autoxidation product formation still needs further validation based on recent experiments (e.g., Quéléver et al, 2019).…”
Section: Temperature Dependencementioning
confidence: 99%